PELAKSANAAN PEMBELAJARAN MENULIS TEKS PROSEDUR PADA SISWA KELAS VII SMP LKIA PONTIANAK - Windy Lia Lestari; Martono Martono; Abdussamad Abdussamad (Universitas Tanjungpura, 2019)
AbstractThis research was based on the application of Curriculum 2013 which was still relatively new in SMP LKIA Pontianak. This research aimed to describe how student learn to write procedure texts that include, planning, implementation and assessment carried out by the teacher. The results of this research indicate that 1) The lesson plan made by the teacher concluded as good enough, appropriate and meets the criteria. 2) the teaching learning process has fulfilled the components of Curriculum 2013 by using scientific approach with discovery learning models from preliminary activities, main activities and closing activities. 3) the assessment / evaluation in learning procedure text has been well applied. The three aspects of the problem were measured using 4 predicate levels, which were very good, good, sufficient, and deficient. The conclusions in this research were planning, implementation, and assessment of the lesson plan which were the main problems in this research had been already good because they have fulfilled the main components of Permendikbud No 22 Tahun 2016 which was the basis of this research assessment, although there were still several aspects that need to be improved. Keywords: Curriculum 2013, Learning, Procedure Texts